Cadmium toxicity induced contrasting patterns of concentrations of free sarcosine, specific amino acids and selected microelements in two Noccaea species - Zemanová, Veronika; Pavlík, Milan; Pavlíková, Daniela (PloS one, 2017)
Cadmium (Cd) toxicity affects numerous metabolic processes in plants. In the presence of Cd, plants accumulate specific amino acids which may be beneficial to developing Cd tolerance. Our study aimed to characterize the changes in the metabolism of selected free amino acids that are associated with Cd tolerance, and investigate the levels of selected microelements in order to relate these changes to the adaptation strategies of two metallophytes-Noccaea caerulescens (Redlschlag, Austria) and Noccaea praecox (Mežica, Slovenia). The plants were exposed to Cd contamination (90 mg Cd/kg soil) for 120 days in a pot experiment. Our results showed higher Cd accumulation in N. praecox compared to N. caerulescens. Cadmium contamination reduced the zinc and nickel levels in both species and a mixed effect was determined for copper and manganese content. Differences in free amino acid metabolism were observed between the two metallophytes growing under Cd-free and Cd-loaded conditions. Under Cd-free conditions, aromatic amino acids (phenylalanine, tryptophan and tyrosine) and branched-chain amino acids (leucine, isoleucine and valine) were accumulated more in the leaves of N. praecox than in N. caerulescens. Cd stress increased the content of these amino acids in both species but this increase was significant only in N. caerulescens leaves. Marked differences in the responses of the two species to Cd stress were shown for alanine, phenylalanine, threonine and sarcosine. Cadmium contamination also induced an increase of threonine as alanine and sarcosine decrease, which was larger in N. caerulescens than in N. praecox. All these factors contribute to the higher adaptation of N. praecox to Cd stress.
Keywords: fyziologický stres; sarkosin; Stress, Physiological; Trace Elements; Metabolic Networks and Pathways; metabolické sítě a dráhy; Amino Acids; Brassicaceae; aminokyseliny; Plant Leaves; kadmium; stopové prvky; listy rostlin; Sarcosine; Cadmium